A cold-set wood adhesive based on soy protein. (April 2021) - Mousavi, Seyyed Yahya; Huang, Jian; Li, Kaichang
Abstract: In this study, combinations of bisphenol A diglycidyl ether (BPADGE) and polyethylenimine (PEI) were investigated as effective crosslinking agents for soy protein isolate (SPI) at room temperature. Three-ply plywood panels were prepared with the SPI-BPADGE-PEI adhesives via a cold press process and were evaluated for their water resistance and shear strengths in accordance with the requirements of the American National Standard for Hardwood and Decorative Plywood for exterior applications. The effects of BPADGE/(SPI + PEI) weight ratio, SPI/PEI weight ratio, solids content of the adhesive, the rate of adhesive usage, and the press time at room temperature on the water resistance and the shear strengths of plywood panels were investigated. The pot-life of the adhesive was also measured. Plywood panels bonded with the SPI-BPADGE-PEI adhesives met the industrial requirements for exterior applications.